PENGUJIAN ALAT DESTILASI MINYAK SEREH DENGAN KAPASITAS 10 KG - Tridaya, Mogi Tridaya; Yudisworo, Djoko; Lazuardy, Dedi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2024)
Testing of a 10 kg capacity lemongrass oil distillation apparatus was carried out to evaluate the performance and efficiency of the distillation process. This study includes setting main parameters such as distillation temperature, process time, and type of raw material used. The main goal is to ensure that the distillation equipment can produce lemongrass oil with optimal quality according to its capacity. The testing method involves measuring the distillation results in terms of citronella oil yield and chemical composition. This analysis provides in-depth insight into the effectiveness of distillation equipment in maintaining the quality of the lemongrass oil produced. The test results show that setting the temperature and distillation time has a significant effect on the final result, with certain conditions producing better quality lemongrass oil. The implication of this research is the importance of an in- depth understanding of operational parameters in the distillation process to maximize the production of consistently high quality lemongrass oil.